2022
DOI: 10.3390/ijerph19042149
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Preferences for Pharmacological versus Psychological Interventions among Primary Care Providers in Nepal: Mixed Methods Analysis of a Pilot Cluster Randomized Controlled Trial

Abstract: There is increasing evidence supporting the effectiveness of psychological interventions in low- and middle-income countries. However, primary care providers (PCPs) may prefer treating patients with medication. A secondary exploratory analysis of a pilot cluster randomized controlled trial was conducted to evaluate psychological vs. pharmacological treatment preferences among PCPs. Thirty-four health facilities, including 205 PCPs, participated in the study, with PCPs in 17 facilities assigned to a standard ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The visual recovery narratives presented by the persons with lived experience as well as other forms of structured social interaction of persons with lived experience are incorporated into mental health trainings for PHC staff. A pilot study showed that incorporating these social contact components into PHC trainings reduced stigma, increased MHC diagnostic accuracy of HCPs, and increased willingness to endorse and deliver psychological and psychosocial treatments (i.e., not solely rely upon medication) [ 42 , 43 ]. The RESHAPE intervention is now being piloted in Tunisia, Ethiopia, India, and China.…”
Section: Discussionmentioning
confidence: 99%
“…The visual recovery narratives presented by the persons with lived experience as well as other forms of structured social interaction of persons with lived experience are incorporated into mental health trainings for PHC staff. A pilot study showed that incorporating these social contact components into PHC trainings reduced stigma, increased MHC diagnostic accuracy of HCPs, and increased willingness to endorse and deliver psychological and psychosocial treatments (i.e., not solely rely upon medication) [ 42 , 43 ]. The RESHAPE intervention is now being piloted in Tunisia, Ethiopia, India, and China.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed methods evaluation of the pilot cRCT demonstrated feasibility and acceptability of the RESHAPE implementation strategy. Qualitative narratives demonstrated that the PCPs felt they better understood the experience of patients and felt more confident that they could diagnose and treat such patients after hearing the recovery narratives [32,[38][39][40][41]. They also had more willingness to initiate psychological services [41].…”
Section: Preliminary Studies Of the Reshape Implementation Strategymentioning
confidence: 99%
“…These findings align with evidence indicating psychological interventions are effective in LMIC (Cuijpers et al ., 2018 ; Karyotaki et al ., 2022 ) and may have more enduring effects than antidepressants alone for people with depression (Cuijpers et al ., 2013 ). Despite this, there is evidence primary care providers in Nepal prefer pharmacotherapy to psychological or psychosocial interventions when treating depression (Bhardwaj et al ., 2022 ).…”
Section: Introductionmentioning
confidence: 99%